The color and scent of sale a quasi experimental research on the effect of visual-olfactory relationship in the visual merchandising of female apparel stores - Bantayan, Joanne Christine D.; Mayo, Adelaida Villaraza (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study, following a quasi-experimental research method, examined the effect of the application of color and odor as visual merchandising strategies in selected female apparel store interiors. Using purposeful sampling, four female apparel stores were purposefully chosen as the controlled environments to where twenty (20) respondents were subjected during the experiment. Two of these stores applied both color and odor in their interior while the remaining two only applied color. A multi-method approach, using survey-questionnaires, observation sheets and photo documentation, was organized to acquire data. Using the concept of the gestalt triangle, results and findings suggest that while the application of color and odor to the store interior as promotional strategies may have a positive effect on most of the respondents‟ perception of the female apparel stores in terms of their store image, there were also cases obtained when some of the respondents challenge the reaction by showing a negative response based on their personal preferences. Hence, it is recommended that the future researcher select respondents who represent a broader market of female apparel stores so as to clearly identify a general set of agreeable colors and odors that can be applied to store interiors regardless of the respondents‟ individual preferences. Finally, this study challenges interior designers, architects and visual merchandisers to see the potential of applying and combining sensory elements in retail design by exploring the use of other sensory modalities in the visual merchandising of female apparel stores.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Display of merchandise; Women's clothing -- Merchandising